2017
DOI: 10.1161/hypertensionaha.117.10150
|View full text |Cite
|
Sign up to set email alerts
|

Placental Growth Factor as a Prognostic Tool in Women With Hypertensive Disorders of Pregnancy

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…Notably, PlGF seemed to have relatively poor predictive potential for late‐onset disease (sensitivity: 45%), likely rooted in a lesser role for defective placentation in late‐onset pathogenesis . In 2017, Ukah et al published results from a systematic review of studies that investigated the potential for PlGF to predict maternal and fetal complications in hypertensive disorders of pregnancy . They found that PlGF was useful for predicting fetal complications (including preterm delivery and adverse neonatal outcomes), with AUC of ≥0.70, although PlGF did not produce a clinically significant improvement in the prediction of adverse maternal outcomes.…”
Section: Predictive Tests Utilizing Angiogenic Factorsmentioning
confidence: 99%
“…Notably, PlGF seemed to have relatively poor predictive potential for late‐onset disease (sensitivity: 45%), likely rooted in a lesser role for defective placentation in late‐onset pathogenesis . In 2017, Ukah et al published results from a systematic review of studies that investigated the potential for PlGF to predict maternal and fetal complications in hypertensive disorders of pregnancy . They found that PlGF was useful for predicting fetal complications (including preterm delivery and adverse neonatal outcomes), with AUC of ≥0.70, although PlGF did not produce a clinically significant improvement in the prediction of adverse maternal outcomes.…”
Section: Predictive Tests Utilizing Angiogenic Factorsmentioning
confidence: 99%
“…Importantly, the natural history in terms of risks for mother and fetus are also highly variable, and the ability to predict these risks is an important priority. Consequently, the obstetric and cardiology communities have made joint calls to try and effectively utilize prognostic indicators as a strategy to identify, classify and guide treatment for hypertensive disorders of pregnancy 6, 7, 8. To effectively translate current knowledge and develop effective pathway‐specific therapeutic strategies, the predictive value of clinical characteristics, maternal hemodynamic and placental indicators must be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…cessation of PlGF synthesis(20,(48)(49)(50). In the setting of hypertensive disorders of pregnancy, a recent review by Ukah et al demonstrated that lower PlGF levels were predictive of poorer neonatal outcomes and preterm birth(1). Recent literature also suggests that a similar hypoxic process secondary to suboptimal placental function and reflected by lower levels of maternal PlGF may also be present later in pregnancy causing late-onset FGR and intrapartum fetal compromise culminating in adverse neonatal outcomes(8,13,44).…”
mentioning
confidence: 99%